An Assessment of the Current Diagnostic Criteria for Infective Endocarditis - Albert W Chan; Heather J Ross (Canadian Journal of Infectious Diseases)
A firm diagnosis of infective endocarditis is difficult to establish. Clinicians often face a decision-making dilemma about whether to treat a patient presenting with some features that suggest endocarditis. This article summarizes both the previous and the recently proposed criteria for the diagnosis of infective endocarditis, and reviews the efficacy of the new criteria. The authors also discuss the experience at The Toronto Hospital, Toronto, Ontario, with this disease, paying specific attention to the application of the new criteria in the diagnostic process.